Power quality improvement based on hybrid coordinated design of renewable energy sources for DC link channel DSTATCOM - Ali Nasser Hussain; Ahmed Jadaan Ali; Firas Saaduldeen Ahmed (Institute of Advanced Engineering and Science, 2020)
This paper presents a comprehensive analysis of power quality for static synchronous compensator on the distribution power system (DSTATCOM) when a different types of energy sources are used to supply the dc link channel of DSTATCOM. These types of power supplies have a different effect on the compensation of DSTATCOM due to operation nature of these sources. The dynamic response of the DSTATCOM has been investigated that produced by individual and hybrid energy sources to evaluate the influence of these sources in terms of time response, compensation process and reduce the harmonics of current for source. Three cases have been considered in this study. First the photovoltaic (PV) cells alone second the battery storage alone and third a hybrid coordinated design between (PV cells with battery storage) is used. A boost Dc-Dc circuit has been connected to a photovoltaic cell with Maximum Power Point Tracking (MPPT) while a Dc-Dc buck-boost circuit is used with a battery. High coordination between PV and battery circuits in the hybrid system is used in order to improve the performance. A synchronous reference frame (SRF) with unit vector has been used to control the STATCOM circuit. The simulation results show that the hybrid design has the superiority response compared to the individual sources.